The impact of Artificial Intelligence on Customer Loyalty in Moroccan companies - CHOUIEKH Nihal; BELBACHIR Mohammed (African Scientific Journal, 2025)
Abstract In a constantly changing world, competitiveness is becoming more and more pronounced. Consumer behavior has changed and the purchasing and payment methods are becoming more digitalized. Thus, the use of a well-defined strategy to attract, satisfy and retain customers is essential. Hence, the integration of AI into this process is an inevitable opportunity. With this in mind, this paper focuses on the confidentiality of consumer information and their behavior in order to satisfy and retain them through AI. To do this, this article is divided into three main parts. A theoretical overview as well as the development of variables and the presentation of hypotheses constitute a decisive phase in us. Then, it is wise to stimulate the methodology chosen for our research, the development and administration of questionnaires as well as the software for processing the data collected. The last part is reserved for the interpretation, discussion of the results as well as the proposal of suggestions intended for entrepreneurs and managers. In this regard, a hypothetical-deductive reasoning is adopted, as well as a questionnaire was administered to 50 companies in the Casablanca-Settat region. The data were processed by the statistical software SPSS version 26. In addition, the data relating to the respondents and the companies were illustrated via graphical representations. However, ANOVA, file and correlation tests are interesting in our case. The results of the correlation have specified the importance of AI in the social field, the confidentiality of customer information and their loyalty. In addition, a summary of the process of developing this test as well as determining the situation of the hypotheses and the implication and the limits are judicious to finalize this research. Keywords : Artificial intelligence (AI) ; Customer satisfaction ; Social sphere ; Moroccan company; SPSS.